Judicial Scrutiny Under Indonesia’s KUHAP 2025: Transplantation and Institutional Incoherence - Afandi, Fachrizal; Bagaskoro, Ladito Risang (Faculty of Law, Universitas Brawijaya, 2026)
Law No. 20 of 2025 on Criminal Procedure (KUHAP 2025) represents Indonesia’s most significant criminal procedure reform following KUHAP 1981. The new Code expands the scope of pre-trial review (praperadilan) and recognises suspect designation as a coercive measure and introduces specific evidentiary consequences for certain unlawful investigative acts. These reforms indicate genuine normative progress. However, this article argues that the effectiveness of judicial scrutiny under KUHAP 2025 depends on institutional coherence between review mechanisms, investigative authority, access to information, and remedies. Using normative legal research and functional comparative analysis, this article compares Indonesia with the United States federal pre-trial motion system and the Dutch rechter-commissaris model. The comparison shows that KUHAP 2025 selectively adopts adversarial legal style features, such as broader pre-trial review and limited exclusionary consequences, without establishing the supporting infrastructure of adversarial litigation, including structured disclosure and robust suppression practice. Simultaneously, it does not create an examining judge comparable to the Dutch model or an automatic mechanism for prompt judicial review of arrest and detention. As a result, judicial scrutiny remains largely reactive, application-based, and dependent on executive-controlled information. The article concludes that KUHAP 2025 modernises the language of rights protection but risks producing procedural hybridity without institutional coherence, unless judicial authorisation and pre-trial review are interpreted as substantive protection against coercive power before conviction.